Quasi-biennial variations in the winter-time circulation of high latitudes - Reiter, Elmar R., author; MacDonald, Bruce C., author; Springer-Verlag, publisher (Colorado State University. Libraries, 1973)
In the years between 1952 and 1962 a quasi-biennial modulation became apparent in the total ozone values measured over Arosa, Switzerland, during spring. The stratospheric vortex behavior in the northern hemisphere during March of the years 1958 to 1964 also showed a biennial variation. This has led to speculations that the quasi-biennial forcing of the tropical stratosphere may extend its influence to the stratosphere and troposphere of high latitudes. It is shown in this paper that the stratosphere and troposphere of high latitudes in the northern hemisphere, indeed, are coupled by a "feedback" mechanism. The forcing from tropical latitudes, however, seems to be minimal.
Keywords: Atmospheric circulation; Winds; Dynamic meteorology; Stratosphere -- Observations; Troposphere -- Observations